Prevalence of Hypoalbuminemia in Chronic Kidney Disease Patients on Hemodialysis - Haris Raza; Abdul Shakoor Shakir; Rizwan Zafar (Medical Journal of South Punjab, 2024)
Objective: To determine the prevalence of hypoalbuminemia in chronic kidney disease patients on hemodialysis.Methodology: A Cross-sectional study was conducted in the Hemodialysis unit of Farooq Hospital, Lahore, from August 1st, 2023, to February 1st, 2024. Four hundred patients with chronic renal disease who had been on hemodialysis for the last 03 months were enrolled in the study. After recording the baseline and relevant history, patients were enrolled, and their blood samples for serum albumin were withdrawn. Hypoalbuminemia was labeled based on serum albumin ?3.5 g/dL. The prevalence of hypoalbuminemia was presented as frequency and percentage.Results: The mean age of the patients was 47.05±12.42 years, mean BMI was 25.53±4.48 kg/m2. There were 235 (58.8%) males.  Hypertension and diabetes were observed in 166 (41.5%) and 121 (30.3%), respectively. The prevalence of hypoalbuminemia was 149 (37.3%). Of the 149 patients, 49 (32.9%) had mild, 73 (49.0%) had moderate, and 27 (18.1%) had severe hypoalbuminemia. Hypoalbunemia had a significant association with the age group, gender, hypertension, and diabetes on data stratification.Conclusion: Hypoalbuminemia is prevalent in a significant population of patients with chronic kidney disease undergoing hemodialysis.